Improvement of colloidal stability in colloidal processing for highly translucent, nanosized zirconia - Chin, Chuin Hao; Andanastuti Muchtar,; Che Husna Azhari,; Masfueh Razali,; Mohamed Aboras, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study aimed to improve the colloidal stability of yttria-stabilized tetragonal zirconia polycrystalline (Y-TZP) suspension through colloidal processing to obtain highly translucent Y-TZP. Agglomeration is often the main complication in the processing of nanosized Y-TZP as it deteriorates mechanical and optical properties. Thus, colloidal processing is necessary to mitigate the agglomeration in Y-TZP. The colloidal stability of Y-TZP suspension plays a key role for the success of colloidal processing. In this study, colloidal processing was conducted at several stages, namely, dispersant addition, pH adjustment and sedimentation. Changes in particle size and zeta potential at various stages were recorded. The suspensions were then slip-casted to form green bodies. Green bodies were sintered and characterized for density and translucency. The results showed that dispersant addition followed by pH adjustment effectively dispersed soft agglomerates by introducing electrosteric stabilization, whereas sedimentation successfully segregated hard agglomerates and contributed excellent colloidal stability. With high colloidal stability, the translucency of Y-TZP was improved by approximately 30%. This study demonstrated different colloidal processing stages and proved that high colloidal stability and fine particle size are vital to produce highly translucent Y-TZP.